2011
DOI: 10.1080/02687038.2011.626845
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the use of graphics in written health information for people with aphasia

Abstract: Background: One of the documented design features of aphasia-friendly written information is the inclusion of graphics. People with aphasia have identified a preference for the inclusion of photographic illustrations in printed education materials (PEMs); however this preference contrasts with research suggesting that line drawings may be a more effective graphic type. Few studies have explored how graphics affect reading comprehension for people with aphasia. Aims: The aims of this research were (1) to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 42 publications
4
23
1
Order By: Relevance
“…Dietz et al (2009) found that photographs had a significantly positive effect on reading comprehension, measured by asking seven participants with aphasia to read a series of narratives and answer related sets of comprehension questions. In contrast, Rose et al (2011b) reported that in their study of 22 people with aphasia neither line drawings nor photographs had a significant effect on the comprehension of written paragraphs.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Dietz et al (2009) found that photographs had a significantly positive effect on reading comprehension, measured by asking seven participants with aphasia to read a series of narratives and answer related sets of comprehension questions. In contrast, Rose et al (2011b) reported that in their study of 22 people with aphasia neither line drawings nor photographs had a significant effect on the comprehension of written paragraphs.…”
Section: Introductionmentioning
confidence: 84%
“…These results align with previous evidence (Rose et al . ), however they require careful consideration in light of the study limitations and further investigation. One possible explanation is that participant's ability to comprehend nouns was already at ceiling, therefore there may not have been scope for the images to have a significant impact on comprehension.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants with aphasia were provided with a user manual containing instructions on the operation of the tablet, mobile broadband device, and eSALT program for reference at home. This user manual was formatted according to aphasia-friendly guidelines outlined by Rose et al (2011). Participants with aphasia were also supplied with the contact details of the lead researcher (AH) and their clinician and were encouraged to make contact if technical issues arose during the trial period.…”
Section: Methodsmentioning
confidence: 99%
“…Separate information and consent forms were developed for clinician participants and the participants with aphasia. The information sheet for the participants with aphasia was formatted according to the aphasia-friendly guidelines outlined by Rose et al (2011). If required communication support techniques as outlined by Kagan (1998) were employed to facilitate understanding and ensure informed consent was obtained.…”
Section: Ethics Statementmentioning
confidence: 99%